Effectiveness and impact of the walking bleach technique on esthetic self-perception and psychosocial factors: A randomized double-blind clinical trial - Bersezio, C. [UNESP]; Martin, J.; Peña, F.; Rubio, M.; Estay, J.; Vernal, R.; Oliveira, O. B. [UNESP]; Fernández, E. (Operative Dentistry, 2017)
Objective: This trial evaluates the impact of psychosocial and esthetic self-perceptions of patients undergoing nonvital tooth bleaching using the walking bleach technique. We also assessed the clinical effectiveness of bleaching tooth discoloration. Methods: Fifty volunteers with nonvital tooth discoloration were enrolled. Teeth were randomized into two groups: 35% hydrogen peroxide (n=25) and 37% carbamide peroxide (n=25). Intracoronal bleaching was performed over four sessions using the walking bleach technique. Tooth color was evaluated at each session to measure total color variation. The shade guide was arranged from highest (B1) to lowest (C4) values to assess the color and calculate the color change in the number of shade guide units. Subjective and objective assessments were compared with the tooth counterpart. Esthetic self-perception and psychosocial factors were assessed before and after treatment. Results: Color change was 15.48,5.17 from hydrogen peroxide and 14.02,4.85 from carbamide peroxide. There was no significant difference at any time point (p.0.05) except at sessions 3 and 4 (p<0.05). Overall, whitened teeth values were similar to those of counterpart teeth (p.0.05). There was a decrease in Oral Health Impact Profile and Psychosocial Impact of Dental Esthetics questionnaire scores after treatment compared with baseline (p<0.05). Conclusion: The walking bleach technique was highly effective on nonvital teeth and had a positive effect on self-esthetic perception and psychological impact from the patients.